The Implementation of cooperative Learning Method in Sport Physiology Course - Norito, Tri Bayu; Satriawan Chan, A. Apri (Athena: Physical Education and Sports Journal, 2025)
This study aims to implement the cooperative learning method in the Department of Sports Education and Coaching JPOK, University of Jambi, as a process of actualizing ASN values. This learning method aims to increase student involvement, understanding of the material, and collaboration between lecturers and students. These activities include the preparation of flexible RPS, provision of interactive Teaching Materials, development of learning media, evaluation of learning methods, and Focus Group Discussions (FGD). In accordance with the results of the implementation, student involvement in learning has increased, understanding of the material has improved, and values, including professionalism, accountability and collaboration, have been strengthened. Therefore, the development of active learning methods must continue to be considered and developed to support JPOK's vision as an innovative and competitive education center.